[Accepted version, unedited] Unmet needs for management of drug resistant infections - Monica Sharma; Kamini Walia; Nitin Bansal (AboutScience Srl, 2022)
Multidrug resistant infections are serious threat globally which demands effective and cost-effective solutions to meet the unmet needs in their diagnosis and treatment. Gram-negative pathogens have been reported as  predominant cause of resistant Infections in developing countries including India. Here, we discuss the priority pathogens and conditions for which feasible solutions adaptable to low resource settings are required to address the resistance in pathogens. These solutions will be helpful in containing spread of antimicrobial resistane and better patient outcomes.